OP0288 PARE WHAT DO YOUNG PEOPLE THINK ABOUT CONTINUOUS DATA COLLECTION IN CLINICAL RESEARCH AND THE TYPES OF ELECTRONIC DEVICES?. (June 2019) - Lunt, Laura; Shoop-Worrall, Stephanie; Khanom, Sonia; Bolger, Imogen; Fantana, Antoniu L; Short, Mary A; Mcdonagh, Janet
Abstract : Background: The use of wearable devices are of increasing interest to enable continuous data collection during drug trials. This is particularly pertinent when involving young people who are "digital natives" and have grown up with such technologies. Objectives: To ascertain opinions from young people regarding the design of wearable devices and the use of continuous data collection for a future clinical drug trial for juvenile idiopathic arthritis (JIA). Methods: A three hour face-to-face patient involvement session was held in a young person friendly venue in central Manchester on the 8 th December 2018. Young people with a rheumatic disease were invited to participate using event flyers provided in local rheumatology clinics. Members of a national youth advisory panel, Your Rheum, were also invited to attend. Data was collected in both large and small group discussions and included a ranking exercise involving the use of voting cards, emojis and pictures of electronic devices to aid conversations. In addition, an online survey was also developed and uploaded to http://yourrheum.org for young people to complete if they could not attend the event in person. Open questions (requesting free text answers) ranged from general thoughts and concerns about continuous data collection, device preferences and features, to examples of unattractive devices. Results: Eight young people attended the event (M=5, F=3, 11-19 age range). All males were under 14 years of age. One young person completed the online survey (F=1). All participants regularly used some form of an electronic device and were generally willing to use a wearable device for continuous data collection, although consideration of school regulations (e.g. uniform policies) and potential bullying was necessary. Participants reported that they would choose a device based on its viability, look, comfort and functionality. For instance, the device would need to be discrete in terms of size, muted (no sounds or vibrations) and removable. The preference of device type differed by gender though a watch and patch were in the top three favourite devices for all. Key features included the ability to switch devices on and off, send reminders, chat to other young people and to track their own data. Some caution was expressed about a device monitoring sleep (or other behaviours that parents may want to know about). It was important for participants to know where the data will be stored, who had access to it and what the information will be used for. Conclusion: Young people have clear opinions as to what they like and don't like with respect to wearable data collection devices. As well as personal preferences, age specific considerations were highlighted by the young people. It is therefore imperative not only to involve young people as research participants but also to involve them at early stages of research including trial design to ensure acceptability of data collection methods including the design of any devices proposed. Acknowledgement: Your Rheum is the national youth advisory panel of the Barbara Ansell National Network for Adolescent Rheumatology BANNAR. We would like to thank all of the young people who took part and other individuals who facilitated their involvement including BANNAR members and Versus Arthritis Young People Coordinators. Disclosure of Interests: Laura Lunt Grant/research support from: Your Rheum is funded by the Arthritis Research UK grant 20164, via the Centre for Adolescent Rheumatology at UCL. The event described here was funded by Eli Lilly., Stephanie Shoop-Worrall Grant/research support from: Your Rheum is funded by the Arthritis Research UK grant 20164, via the Centre for Adolescent Rheumatology at UCL. The event described here was funded by Eli Lilly., Sonia Khanom Grant/research support from: Your Rheum is funded by the Arthritis Research UK grant 20164, via the Centre for Adolescent Rheumatology at UCL. The event described here was funded by Eli Lilly., Imogen Bolger: None declared, Antoniu L Fantana Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Mary A Short Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, janet McDonagh Grant/research support from: Your Rheum is funded by the Arthritis Research UK grant 20164, via the Centre for Adolescent Rheumatology at UCL. The event described here was funded by Eli Lilly., Consultant for: The event described here was funded by Eli Lilly.